Determining the perceived stress levels of nurses during COVID 19 infection in Turkey - Kayaoğlu, Kübra; Aslanoğlu, Eren (My University, 2021)
This study was conducted to determine the stress levels of nurses working during COVID-19 infection. This descriptive study was conducted with 233 nurses. “NurseInformation Form” and “Perceived Stress Scale” were used to collect the data. Percentage, frequency, independent samples t-test, analysis of variance, and Shapiro-Wilktest were used to evaluate the data. It was determined that PSS total score of the participants was 26.22±6.14 (high level). PSS total mean scores of the female nursesworking during COVID-19 infection were significantly higher than the scores of the male nurses (p?0.05). The nurses, who believed that they had enough knowledgeabout COVID-19 infection, had significantly a lower PSS total mean score when compared to the others (p?0.05). It was determined that the stress levels of the nursesworking during COVID-19 infection were high.
Keywords: Sağlık Politikaları ve Hizmetleri; Hemşirelik; Psikoloji